Assessment of Antibacterial Potentials of Lawsonia inermis L. (Henna) Leaf Aqueous Extracts - Garba, M. U.; Adamu, F. U.; Mairami, F. M.; Basheer, A.; Aminu, M. A.; Bukar, F. M.; Yakubu, U. I.; Nura, S. (UMYU Journal of Microbiology Research)
Study’s Excerpt: